'n Verdediging van die Terugverdienperiode-metode as 'n Beoordelingsmaatstaf by Kapitaalinvesteringsprojekte - I. J. Lambrechts (South African Journal of Business Management, 1972)
The evaluation of capital investment projects is one of the main pillars of company profitability. The financial evaluation of projects by the recoupment-period method is universally accepted, but is however often subject to severe criticism.